The Wiley Blackwell companion to religion and peace - Mitchell, Jolyon P.; Millar, Suzanna; Po, Francesca; Percy, Martyn (The Wiley Blackwell companions to religion, 2022)
"This growing recognition correlates to the recent rise of Peace Studies, which has developed into a multi-disciplinary and interdisciplinary field of research and teaching. Questions related to peace-making, peacekeeping, and peacebuilding, as well as conflict prevention, conflict transformation, and reconciliation, are commonly raised not only in Peace Studies, but also in a range of other disciplines such as International Relations, History and Politics, as well as Theology and Religious Studies. While there are obviously both similarities and dissimilarities among and within different evolving religious traditions, all world religions include visions and values of peace, alongside principles for and practices of building peace. As observed earlier, the relationship between religion and violence has attracted far greater scholarly attention than the connections between religion and peace. For example, The Blackwell Companion to Religion and Violence (2011), edited by Andrew R. Murphy, provides an overview and guide to the ever-expanding field of study analysing the relationship of religion and violence, drawing on expertise from many contexts and disciplines. This Companion to Religion and Peace provides an interdisciplinary book addressing key concepts, history, theories, models, resources, and practices in the complex and ambivalent relationship between religion and peace. Contributions are drawn from a range of perspectives and locations, reflecting diverse methods and approaches currently proliferating in research and practice. There is by no means a single unified voice; different authors take significantly different approaches. This collection is grounded in experience and context, drawing on established, developing, and new research"--